PENGARUH MAGNETIK Fe3O4 PADA SERBUK KARBON TERHADAP TINGKAT PENYERAPAN LIMBAH LOGAM Fe - Nur Akmal; Erman Taer; Sugianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The study on synthesis and characterization of magnetic carbon from mixture of rubber wood sawdust and for heavy metal of Fe absorption on the Siak river water samples has been done. The process of milling and seaving resulted a smallcarbon particle size of 38 μm, the increase in surface area of the carbon has beenachieved by chemical activation using the KOH Activator with weight ratio of carbonpowder of 4: 1. After that, carbon powder that had been activated was mixed to by comparison of 5: 4. The mixing process was done using a mortar and continued toballmiling process for 2 hours. Finally, a mixture of carbon powder and was carbonized at temperature of 850oC in N2 gas and then proceed to washing and drying proceses in order to produce carbon magnetic . Absorption testing of heavy metal of Fe in Siak river water samples was performed with variations in immersing time of ½ hours, 1 hour, and 2 hours. Atomic absorption spectroscopy test results revealed that absorption after 2 hours increased from 34,17% (without to 39,63% (using magnetic . Characterization of x-ray diffraction showed the peak of Fe at 2θ = 46,28o and scanning electron microscopy showed uniform particle size with irregular shape and whitish color. Results of Dispersive X-Ray Energy (DXE) proved the existence of metal Fe in magnetic carbon absorbent material from rubber wood sawdust.